2010
DOI: 10.1074/jbc.m109.078667
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Citrate-binding Site of Human ATP-Citrate Lyase Using X-ray Crystallography

Abstract: ATP-citrate lyase (ACLY, EC 2.3.3.8) 3 catalyzes the reaction, citrate ϩ CoA ϩ ATP 3 acetyl-CoA ϩ oxaloacetate ϩ ADP ϩ P i , in the presence of magnesium ions (1). ACLY is the cytoplasmic enzyme linking energy metabolism from carbohydrates to the production of fatty acids. Acetyl-CoA produced in the mitochondria cannot be exported to the cytoplasm. Instead, acetylCoA in mitochondria is transformed to citrate by citrate synthase, and citrate is exported to the cytoplasm where ACLY regenerates acetyl-CoA. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 57 publications
4
64
1
1
Order By: Relevance
“…1I). These two domains have been reported to be crucial for ACLY activity (Sun et al 2010). These results together demonstrate that ACLY directly interacts with KLHL25 to form a complex with CUL3 in cells.…”
Section: Acly Interacts With Cul3 and Klhl25 To Form A Complexsupporting
confidence: 56%
“…1I). These two domains have been reported to be crucial for ACLY activity (Sun et al 2010). These results together demonstrate that ACLY directly interacts with KLHL25 to form a complex with CUL3 in cells.…”
Section: Acly Interacts With Cul3 and Klhl25 To Form A Complexsupporting
confidence: 56%
“…A comparable mode of interaction of the Ac group of Ac-CoA interacting with ACLY or ckcACD1, respectively, might be assumed. Hence, we superimposed ckcACD1 onto the crystal structure of human ACLY with bound citrate (17). The resulting distance between the carbonyl carbon of Ac-CoA of ckcACD1 and the carbon C1 of citrate in ACLY is ∼2.8 Å.…”
Section: Ckcacd1 and Ecscs Display Very Similar Features For The Catamentioning
confidence: 99%
“…This phenomenon, termed "domain shuffling," is one of the key features of this superfamily (8). Superposition of several structures of SCS from Escherichia coli (ecSCS) (12)(13)(14), Thermus aquaticus (15), the mammalian GTP-specific SCS from pig (16), and a truncated form of human ACLY (17,18) revealed that subdomains 1-5 share a common arrangement in these enzymes. From detailed studies of the reaction mechanism of ecSCS, a crucial enzyme tightly connected to the TCA cycle, a three-step mechanism was proposed, which involves the phosphorylation of a highly conserved His residue at the first active site (site I) as an intermediate step (12,13).…”
mentioning
confidence: 99%
“…NP_001087), residues 2-425 form domains 3, 4, and 5, and all three of these domains are homologous to the β subunit of succinyl-CoA synthetase. Residues 487-820 form domains 1 and 2, which are homologous to the α subunit of succinyl-CoA synthetase (Sun et al, 2010). In the present study, two SNPs g.17127C>T and g.35520C>T identified in bovine ACLY were found to be located in domains 5 and 2 of human ACLY isoform 1, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…In mammals, ACLY is a homotetramer, containing an ATP-grasp domain (N-terminal region), a CoA binding domain, a CoA-ligase, and citrate synthetase (C-terminal region) (Morita et al, 2014). Sun et al (2010Sun et al ( , 2011 successfully identified the citrate and ATP binding site of chymotrypsin-truncated human ACLY using X-ray crystallography, revealing the partial residue conformation of the 1101-amino acid protein.…”
Section: Introductionmentioning
confidence: 99%